Integrating Tithonia Diversifolia, Piper Guineense and Oil Palm Bunch Residue Ash for the Management of Sweet Potato Weevil (Cylas Puncticollis Boh.) and on Yield of Sweet Potato in Fako Division of Cameroon (International Journal of Natural Sciences Research, 2022)
This research was to evaluate the effects of integrating T. diversifolia, P. guineense and OPBRA to manage Cylas puncticollis infestation and on the yield of sweet potatoes. Bioassay 1, 5g T. diversifolia + 5g P guineense /100mL and 10g P guineense /100mL showed significant low (P < 0.05) in mortality, number of eggs laid, percentage repellence and progeny emergence of C. puncticollis. Bioassay 2: 20 g OPBRA /100mL, 5g OPBRA + 5g P guineense /100mL, and 10g P guineense /100mL. The lowest progeny emergence was 5g OPBRA + 5g P guineense /100mL. 5g OPBRA + 5g P guineense /100mL, and 10g P guineense /100mL showed significant difference (P < 0.05) in mortality, mean number of eggs laid of C. puncticollis with the control. Bioassay 3 and 4: showed significant effect (P < 0.05) of T. diversifolia, OPBRA and P. guineense pastes on weight loss due and root sizes to C. puncticollis damage of sweet potato. On the field, sweet potatoes that were treated with 2 ton/ha T. diversifolia + 2 ton/ha OPBRA + 0.33 ton/ha P. guineense and 0.67 ton/ha P. guineense showed significantly (P < 0.05) less infestation than the other treatments. Plants treated with 2 tons/ha T. diversifolia +2 tons/ha OPBRA + O.33 tons/ha P. guineense had the highest yield. The combination of T. diversifolia, OPBRA and small proportion of P guineense could serve as an alternative of source of synthetic pesticides managing C. puncticolis infestation as well as source of organic matter improve soil fertility.